Curing of Cocoa Beans: Fine-Scale Monitoring of the Starter Cultures Applied and Metabolomics of the Fermentation and Drying Steps - Díaz-Muñoz, Cristian; Van de Voorde, Dario; Comasio, Andrea; Verce, Marko; Hernandez, Carlos Eduardo; Weckx, Stefan; De Vuyst, Luc (Frontiers in Microbiology, 2021)
Starter culture-initiated cocoa fermentation processes can be applied to improve the quality of cured cocoa beans. However, an accurate monitoring of the microbial strains inoculated in fresh cocoa pulp-bean mass to assess their contribution to the cocoa bean curing process is still lacking. In the present study, eight different cocoa fermentation processes were carried out with Trinitario cocoa in vessels in Costa Rica to assess the contribution of two candidate yeast starter culture strains, namely Saccharomyces cerevisiae IMDO 050523 and Pichia kudriavzevii IMDO 020508, inoculated in combination with Limosilactobacillus fermentum IMDO 0611222 and Acetobacter pasteurianus IMDO 0506386. A multiphasic approach, consisting of culture-dependent selective plating and incubation, rRNA-PCR-DGGE community profiling of agar plate washes, and culture-independent high-throughput amplicon sequencing, combined with a metabolite target analysis of non-volatile and volatile organic compounds (VOCs), was performed on samples from the fermentation and/or drying steps. The different starter culture mixtures applied effectively steered the cocoa fermentation processes performed. Moreover, the use of an amplicon sequence variant (ASV) approach, aligning these ASVs to the whole-genome sequences of the inoculated strains, allowed the monitoring of these inoculated strains and their differentiation from very closely related variants naturally present in the background or spontaneous fermentation processes. Further, traits such as malolactic fermentation during the fermentation step and acetoin and tetramethylpyrazine formation during the drying step could be unraveled. Finally, the yeast strains inoculated influenced the substrate consumption and metabolite production during all starter culture-initiated fermentation processes. This had an impact on the VOC profiles of the cured cocoa beans. Whereas the P. kudriavzevii strain produced a wide range of VOCs in the cocoa pulp, the S. cerevisiae strain mostly influenced the VOC composition of the cured cocoa beans.